A novel colorimetric and fluorescence turn-on pH sensor with a notably large Stokes shift for its application. (7th August 2018) - Ning, Yaoyao; Wang, Xiaoqing; Sheng, Kangjia; Yang, Lili; Han, Wei; Xiao, Chaoni; Li, Jianli; Zhang, Yongmin; Wu, Shaoping
Abstract : A novel naked-eye colorimetric and fluorescent turn-on pH sensor based on a naphthalenone scaffold was rationally designed and facilely synthesized. Abstract : A novel naked-eye colorimetric and fluorescent turn-on pH sensor based on a naphthalenone scaffold was rationally designed and facilely synthesized. The probe exhibited strong alkaline pH-dependent (p K a = 9.92) behavior, high selectivity, sensitivity, high quantum efficiency ( Φ = 0.64) and rapid response to pH fluctuations (within 1 min) in the range of 9.0–14.0. In addition, probeDDTM displayed a notably large Stokes shift of 198 nm. The response mechanism of the fluorescent probes was proposed to be caused by OH − -induced structural changes from the nonfluorescentDDTM form to the highly emissive addition product (more than 150-fold fluorescence enhancement) along with ICT changes. Live cell imaging data revealed that probeDDTM could be used to selectively monitor pH changes with low cytotoxicity and cell membrane permeability. Therefore, this probe could be used as an effective intracellular pH imaging sensor under extremely alkaline conditions in the biomedical and biological fields.